FORMULATION OF CHITOSAN MEMBRANE COMPOSITION AND STIRRING OPTIMIZATION FOR REDUCING TOTAL SOLID OF PALM OIL MILL EFFLUENT - Sri Wahyuni; Siswanto Siswanto; Soekarno Miswana Putra (Pusbindiklat - LIPI, 2017)
Palm oil mill effluent (POME) is palm oil industry wastewater with high solid content. Waste filtration using chitosan membrane has been investigated to decrease the solid waste, but the final value does not meet the quality standards. Therefore, further development on formulation and optimization of the membrane manufacturing process (composition and stirring speed) are needed. The purpose of this study was to determine the effect of composition and stiring speed on the performance of the membrane in decreasing solid content of POME. Chitosan membrane was prepared by phase inversion method with two supporting materials, namely Poly Ethylene Glycol (PEG) and Poly Vinyl Alcohol (PVA). The variables of this experiment were Chitosan:PVA ratio (40:60, 45:55, 50:50, 55:45 and 60:40 (v/v)) and stiring speed (200 rpm and 250 rpm). Chitosan composite membrane was tested in a cross flow reactor system. The result showed that the highest rejection values of TSS and TDS generated by the membrane on the chitosan and PVA ratio of 50:50 (v: v) at agitation speed of 250 rpm were 96.84% and 97.23%, respectively.